Credit risk modeling using Excel and VBA with DVD - Löffler, Gunter (Gunter Johannes); Posch, Peter N. (Chichester : Wiley, 2010)
The book provides a hands-on introduction to modern credit risk modeling. This edition covers how parameter uncertainty can be dealt with in estimation of portfolio risk as well as comprehensive new sections on the pricing of CDSs and CDOs, and a chapter on predicting borrower-specific loss given default with regression models.
Includes index
nif 23/04/13;nmn 15/05/13; oif 08/09/14
Loans
Keywords: Microsoft Excel (Computer file); Microsoft Visual Basic for applications; Credit -- Management; Credit -- Management -- Mathematical models; Risk management; Risk management -- Mathematical models; Electronic spreadsheets -- Computer programs